COLOR AND HARDNESS COMPARISON BETWEEN PARBOILED AND NORMAL BLACK RICE - Reza Widyasaputra; Elvira Syamsir; Slamet Budijanto (University of Sultan Ageng Tirtayasa, 2019)
Parboiling process had a potency to change the color and rice grain hardness of black rice. Although, this process could reduce the cooking time and improve the texture of black rice. The aim of this research was to compare the color difference and grain hardness from normal black rice and two different parboiled black rice. Cempo Ireng black rice variety as a sample was taken from local farmer in Ciampea, Bogor, West Java, Indonesia. There was normal (without parboiling process) black rice and two kind of parboiled black rice used in this research. First, parboiled black rice X (0% sodium citrate concentration, 5 minute steming time, and 1 time freezing-thawing cycle), parboiled black rice Y (5% sodium citrate concentration, 15 minutes steaming time, and 4 times freezing-thawing cycles). One way Anova, Least Square Difference (LSD) and Independent sample t-test was used to determine the significant differences between mean values. There was significant difference on color parameter between normal and parboiled black rice grain. In cooked rice, there was significant difference on lightness parameter only. The grain of parboiled black rice X was harder than Y.